The Development of Digital Learning Media Based on Canva with a 5W1H Approach to Enhance Short Story Writing Skills Among Elementary School Students in Sintang Regency - Faizat Faizat; Bachtiar Bachtiar (Edumaspul: Jurnal Pendidikan, 2025)
In the digital era, the low writing skills in narrative composition among elementary school students and the lack of engaging learning media present significant challenges in the educational process. This study aims to develop and evaluate the effectiveness of a digital learning medium based on Canva, utilizing the 5W1H approach, to enhance the narrative writing skills of elementary school students in the Sintang District. The research employs the Research and Development (R&D) methodology with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were fifth and sixth-grade students from several elementary schools in Sintang District. The results of expert validation indicated that the media was deemed appropriate for use, with high validity scores. The small-scale and large-scale trials demonstrated a significant improvement in students' narrative writing skills, as evidenced by the pretest and posttest results. This media also facilitated students' understanding of both the intrinsic and extrinsic elements of short stories and contributed to increased motivation and engagement in the learning process. Canva was an effective tool in creating an interactive and innovative learning experience.